الحوكمة في المؤسسات المالية الإسلامية و تطوير الصناعة المالية الإسلامية - لبزة, هشام; ضيف الله, محمد الهادي; خنيش, يوسف (University of eloued جامعة الوادي, 2018)
تهدف هذه الورقة البحثية إلى دراسة دور المؤسسات المالية الإسلامية في تطوير الصناعة المالية الإسلامية، وذلك من خلال تبني أنظمة قوية تساعدها على تحسين أدائها المالي والإداري، وتحقيق ميزة تنافسية كبيرة. ولهذا الغرض، فإنها تستخدم العديد من المناهج الاقتصادية والإدارية لتحقيق أهدافها المختلفة، وأهم هذه المناهج وأكثرها استجابة لاحتياجاتها هو منهج الحوكمة. وفي هذا السياق، نهدف من خلال هذا البحث عن مفاهيم وأهمية ومبادئ الحوكمة، وتحليل فعالية الحوكمة في المؤسسات المالية الإسلامية، وتوضيح دور مبادئالحوكمة في تفعيل وتطوير الصناعة المالية الإسلامية. Abstract: Today, Islamic financial institutions look for develop the Islamic financial industry, and they try to adopt strong systems which help them to improve their financial and managerial performance, and make a significant competitive advantage. For this purpose, they use many economical and managerial approaches to achieve their various objectives, and the most important of these approaches and the most responsive to the their needs is Governance approach. In this context, this research exposes concepts, importance, and principles of governance, and analyzes the effectiveness of governance in Islamic financial institutions, and shows the role of governance systems in the activation and the development of Islamic financial industry.
المالية الإسلامية و التوجيهات الراهنةالتقنية المالية ، الشمول المالي، الأسواق الناشئة جامعة ابن زهر أكادير- المغرب
Keywords: تصنيف، الحوكمة،المؤسسات المالية الإسلامية، الصناعة المالية الإسلامية. JEL: G23, G34, G39; Governance, Islamic Financial Institutions, Islamic Finance Industry. JEL Classification: G23, G34, G39.